Personal branding, product quality, and price as determinants of purchase decisions: the mediating role of marketing strategy in local culinary smes - Cery Zepetiyana; Suhardi Suhardi; Afrizal Afrizal (Economic: Journal Economic and Business, 2026)
This study aims to analyze the influence of personal branding, product quality, and price on purchasing decisions with marketing strategy as a mediating variable in culinary businesses in Pangkalpinang City. The study used a quantitative approach with a survey method of 100 consumers selected through a purposive sampling technique. Data were collected using a five-point Likert scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) assisted by SmartPLS. The results showed that personal branding and product quality had a positive and significant effect on purchasing decisions, while price did not have a significant effect. In addition, personal branding and price had a significant effect on marketing strategy, but product quality did not. Marketing strategy also had no significant effect on purchasing decisions and was unable to mediate the relationship between the independent variables and purchasing decisions. These findings indicate that consumer purchasing decisions are more influenced by the strength of business actor identity and product quality than by price or marketing strategy. This study contributes to the development of purchasing decision models in culinary MSMEs by emphasizing the limited role of marketing strategy as a mediating variable.